Epidemiology, Theories Of The Development, Conservative And Operative Treatment Of The Endometriosis. - Sarkisova Viktoriya Vladimirovna (Peerian Journals Publishing, 2023)
According to modern ideas about the nature of endometriosis, this disease should be considered as a pathological process with a chronic, recurrent course. Endometriosis is formed and develops against the background of impaired immune, molecular genetic and hormonal relationships in the female body
Keywords: Adenomyosis; adenomyoma; epithelial metaplasi; HLA system